Early Detection of COVID-19 Waves From Cases in a Neighboring Country With an Open Border - Kamat, Anil; Sah, Amrita (Frontiers in Public Health, 2021)
Although it has been assumed that there exists a close relationship of COVID-19 virus transmission between the countries with the open border, an empirical analysis is lacking. We present an analysis between Nepal and India; the two neighboring countries with open borders where numerous people and commodities cross the border every day. Here we have used non-linear methods to probe the landscape of correlation between temporal COVID-19 incidences and deaths in these two countries. First, we analyzed the correlation for the whole time series and found the correlation for COVID-19 incidence between these countries is statistically significant and there is a lag of 6 days for maximum correlation. Secondly, we analyzed the correlation for each wave and found the distance correlation for the first phase is 0.8145 with a lag of 2 days and the distance correlation for the second wave is 0.9685 without any lag. This study can be a critical planning tool for policymakers and public health practitioners to make informed decisions on border closure in the early days.